The jumping spiders (Araneae: Salticidae) from the Southwestern region of Central African Republic - Wesołowska, Wanda; Russell-Smith, Anthony; Danflous, Samuel (Zootaxa, 2026)
Only three species of jumping spiders have been recorded from Central African Republic (C.A.R.) to date. The present study is based on materials collected between 2005 and 2012 in southwest C.A.R. Eighty-six species were collected, among them twenty-one are described as new to science: Detalik improcerus sp. nov. (♀), Evarcha fusca sp. nov. (♂), Finger obscurus sp. nov. (♀), Habrocestum mboki sp. nov. (♂♀), Icius ombella sp. nov. (♀), Icius similaris sp. nov. (♂♀), Langelurillus consobrinus sp. nov. (♂), Malizna levis sp. nov. (♀), Malloneta miranda sp. nov. (♂), Phintella pusilla sp. nov. (♀), Pochyta bayanga sp. nov. (♀), Pochyta ceiba sp. nov. (♂), Pseudicius formosus sp. nov. (♀), Schenkelia nocturna sp. nov. (♂), Tarne annoyeri sp. nov. (♂), Thiratoscirtus arbustorum sp. nov. (♂♀), Thiratoscirtus cognatus sp. nov. (♂), Thiratoscirtus iucundus sp. nov. (♀), Thiratoscirtus molongo sp. nov. (♀), Tomomingi blicki sp. nov. (♂♀) and Vicirionessa pulchella sp. nov. (♀). Ugandinella Wesołowska, 2006 is proposed as a junior subjective synonym of Enoplomischus Giltay, 1931. Viciria chabanaudi Fage, 1923 is proposed as a junior subjective synonym of Viciria albocincta Thorell, 1899. Two new combinations are proposed Thiratoscirtus gibbosus (Wesołowska & Edwards, 2012) comb. nov. ex Bacelarella Berland & Millot, 1941 and Enoplomischus formiculus (Wesołowska, 2006) comb. nov. ex Ugandinella. The previously unknown sexes of three species, Icius peculiaris Wesołowska & Tomasiewicz, 2008 (♀), Thiratoscirtus oberleuthneri Seiter & Wesołowska, 2015 (♀) and Thiratoscirtus vilis Wesołowska & Russell-Smith, 2011 (♂), are described for the first time. The updated list of salticids from Central African Republic now rises to 88 species.